Body height estimation based on percutaneous foot length and breadth of javanese females - Mochtar, Nur Mujaddidah; Gunawan, Ari; Artaria, Myrtati Dyah; Andajani, Susilowati (Folia Medica Indonesiana, 2017)
Body height estimation is one of important parameters used for establishing the individuality in cases of mutilated bodies or found body parts. It is not rare that in the cases of mutilation the police authority would only give the body parts or remaining skeletons of the victims. The aims of the study were to find body height estimation formula based on percutaneous of foot length and foot breadth in Javanese females at Surabaya Muhammadiyah University. The type of research design was cross-sectional observational study. Samples were Javanese females student at Muhammadiyah University of Surabaya , which was selected as the sample unit . The samples are in this study was Two-hundred and twenty-two people.The variabel independent of this research are foot length and foot breath, the variabel dependent is body height. Data were analyzed using normality test with Kolmogorov Smirnoff (a>0,05), Pearson correlation test (a<0,05) and linear regression test (a <0,05) to get body height estimation formula. The results of this study is, 1) A significant correlation between foot length and body height (r = 0,731), 2) A significant correlation between foot breadth and body height (r-0,323), 3) A significant correlation between foot length, foot breadth and body height (r=0,732), 4) The body height estimation formula based on foot length is 688,435 +3,745*foot length, 5) The body height estimation formula based on foot breadth is = 1273,002 + 2,942*foot breadth, and 6) The body height estimation formula based on foot length and foot breadth is 695,227 + 3,805*foot length – 0,229*foot breadth. As a conclusion of this study is the obtained estimation formula of body height based on foot length and foot breadth of Javanese females is 695,227 + 3,805*foot length – 0,229*foot breadth.